Long‐term effectiveness of lycopene in the management of oral submucous fibrosis (OSMF): A 3‐years follow‐up study. (23rd July 2020) - Arakeri, Gururaj; Patil, Shankargouda; Maddur, Nagaraj; Rao US, Vishal; Subash, Anand; Patil, Shekar; Gao, Shan; Brennan, Peter A.
Abstract: Background: Long‐term follow‐ups after receiving lycopene therapy for management of oral submucous fibrosis (OSMF) are scarce. The study aimed to assess the long‐term efficacy of lycopene for management of OSMF symptoms. Methods: In this prospective clinical study, 400 clinically diagnosed early OSMF patients were assessed for the efficacy of lycopene in alleviation of burning sensation (BS) and reduced mouth opening (MO) symptoms in comparison to placebo. After 1‐year follow‐up, group A (lycopene group) was divided equally into group A1 and group A2. group A1 patients were retreated with lycopene and the A2 group was followed without retreatment. After 2‐year follow‐up, the Group A2 patients were advised retreatment but not followed as most of the patient did not agree for follow‐up. However, group A1 patients were continued to follow‐up every 6 months for a total three years. Statistical analysis was by independent sample t ‐test and P ‐value <.05 were considered as significant. Results: A statistically significant difference ( P < .05 ) in BS and MO was found between group A and B with lycopene showing better results. At one‐year follow‐up, a statistically significant recurrence in the symptoms was found ( P < .05 ) in the lycopene group (group A). After the second intervention, there was a statistically significant difference in the improvement of symptoms between the group A1 and A2 at 6 months and 1 year ( P < .05) with group A1 (retreatment) showing better results. Conclusions: Treatment with lycopene led to improvement in the symptoms of OSMF in the present study. The results highlight the importance of retreatment of lycopene for its long‐term effect on alleviation the symptoms of OSMF.